Electrodynamics of solids : optical properties of electrons in matter - Dressel, Martin, 1960- (Cambridge University Press, 2002)
The authors of this book present a thorough discussion of the optical properties of solids, with a focus on electron states and their response to electrodynamic fields. A review of the fundamental aspects of the propagation of electromagnetic fields, and their interaction with condensed matter, is given. This is followed by a discussion of the optical properties of metals, semiconductors, and collective states of solids such as superconductors. Theoretical concepts, measurement techniques and experimental results are covered in three interrelated sections. Well-established, mature fields are discussed (for example, classical metals and semiconductors) together with modern topics at the focus of current interest. The substantial reference list included will also prove to be a valuable resource for those interested in the electronic properties of solids. The book is intended for use by advanced undergraduate and graduate students, and researchers active in the fields of condensed matter physics, materials science and optical engineering.